Effect of alcohol frothing agents on the coalescence of bubbles coated with hydrophobized silica particles. (28th July 2015) - Bournival, Ghislain; de Oliveira e Souza, Ludmila; Ata, Seher; Wanless, Erica J.
Abstract: The stability of capillary-pinned bubble pairs covered with hydrophobized particles in aqueous solutions of 1-pentanol or methyl isobutyl carbinol (MIBC) was studied using high-speed cinematography. Glass particles were first rendered hydrophobic by covalently bonding a linear alcohol onto the solid interface to achieve a specific hydrophobicity (i.e. contact angle of 43° measured with the captive bubble on a treated wafer) and effectively avoid the presence of any mobile hydrophobizing surfactant. The resistance to coalescence of the bubbles was measured at different frother concentrations and for various initial bubble interfacial areas covered by particles; with particle coverage not exceeding the contact region between the bubbles. Frother molecules were shown to delay the coalescence of bubbles whereas particles were not present in a sufficient quantity at the interface of the bubbles to provide steric stability. However, in some cases in the presence of MIBC, the particles were believed to act as means of transportation for the frother molecules to the surface of the bubbles thus forcing the local relaxation of the interface, which improved bubble stability. The coalescence of two bubbles released energy causing a rapid motion of the interface. This motion was sufficient to expel a fraction of the attached particles from the interface. The addition of frother, and of particles in some cases, increased the dampening of the oscillatory motion generated by bubble coalescence. In general, damped bubble oscillations were associated with a reduced quantity of particles detaching from the bubble. Although particles were observed to dampen the oscillation of the bubble, they were not as effective as the frother molecules in reducing the detachment of particles upon bubble coalescence. This finding is believed be of relevance for industrial applications such as froth flotation. Highlights: Effect of frothing agents and particles on bubble stability decoupled. Frother adsorbed on particles may be carried to the bubble increasing its stability. Interfacial oscillation caused by bubble coalescence led to particle detachment. Frothers dampened bubble oscillation and effectively reduced particle detachment.